2018
DOI: 10.1371/journal.pone.0192332
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in availability of essential medicines to treat non-communicable diseases in Uganda: A Poisson analysis using the Service Availability and Readiness Assessment

Abstract: ObjectiveAlthough the WHO-developed Service Availability and Readiness Assessment (SARA) tool is a comprehensive and widely applied survey of health facility preparedness, SARA data have not previously been used to model predictors of readiness. We sought to demonstrate that SARA data can be used to model availability of essential medicines for treating non-communicable diseases (EM-NCD).MethodsWe fit a Poisson regression model using 2013 SARA data from 196 Ugandan health facilities. The outcome was total numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 15 publications
9
66
0
Order By: Relevance
“…All eligible studies were cross sectional in nature. Six of the studies (67%) were performed in a single African country (Malawi, Uganda-2 different studies, Nigeria, Ghana, South Africa) [1517, 19, 20, 23]. The rest were multi-country studies performed in both an African country and other LMIC outside Africa [18, 21, 22].…”
Section: Resultsmentioning
confidence: 99%
“…All eligible studies were cross sectional in nature. Six of the studies (67%) were performed in a single African country (Malawi, Uganda-2 different studies, Nigeria, Ghana, South Africa) [1517, 19, 20, 23]. The rest were multi-country studies performed in both an African country and other LMIC outside Africa [18, 21, 22].…”
Section: Resultsmentioning
confidence: 99%
“…Another NCD risk factor survey conducted in 2016 in selected peri-urban and rural areas of Uganda found 95.6% of those identified to have DM in rural areas were unaware of their condition while far fewer (65.0%) were unaware of their health status in urban areas [11]. Adding to this disparity and the challenge to management of these conditions, the 2018 Service Availability and Readiness Assessment survey conducted in Uganda found that availability of HTN and DM medications were limited to health facilities located in urban areas [15].…”
Section: Introductionmentioning
confidence: 99%
“…(1,2) Yet the presence of a given medicine on a national list does not ensure access. (3)(4)(5)(6) High or inconsistent cost, and low or inconsistent availability, are important barriers to access.…”
Section: Introductionmentioning
confidence: 99%